Assessing Drug-Likeness The Natural Compounds of Polar Extract Curcuma xanthorrhiza Rhizome via Lipinski's Rules with SWISSADME Web Tool - Sumardi Sumardi; Suprianto Suprianto (Yayasan Penelitian dan Inovasi Sumatera, 2024)
Curcuma xanthorrhiza, commonly known as Javanese turmeric, is widely recognized for its medicinal properties, with its polar extract containing various bioactive compounds. This study aims to assess the drug-likeness of natural compounds found in the polar extract of Curcuma xanthorrhiza rhizome using Lipinski's Rule of Five, analyzed through the SWISSADME web tool. The compounds alpha pinene, alpha thujene, beta pinene, and zingiberene were evaluated for their physicochemical properties, including molecular weight, hydrogen bond donors and acceptors, lipophilicity, and solubility. The analysis confirms that these compounds meet the criteria for oral drug-likeness. Additionally, specific parameters such as fractionCsp3, iLOGP, and MLOGP were found to significantly influence the permeability of these compounds, further supporting their potential as orally administered therapeutics. The findings underscore the utility of SWISSADME in preclinical screening of natural products, offering a valuable approach to identify promising candidates for drug development. This study highlights the potential of Curcuma xanthorrhiza polar extract as a source of drug-like compounds, paving the way for further pharmacological and clinical investigations.